The predictive value of creatinine clearance for mortality in patients undergoing revascularization - Eilon Ram; Pazit Beckerman; Amit Segev; Nir Shlomo; Abigail Atlas-Lazar; Leonid Sternik; Ehud Raanani (Journal of Cardiothoracic Surgery, 2021)
Abstract Background Renal function plays a significant role in the prognosis and management of patients with multi-vessel coronary artery disease (CAD) referred for revascularization. Current data lack precise risk stratification using estimated glomerular filtration rate (eGFR) and creatinine clearance. Methods This prospective study includes a three-year follow-up of 1112 consecutive patients with multi-vessel CAD enrolled in the 22 hospitals in Israel that perform coronary angiography. Results The Mayo formula yielded the highest mean eGFR (90 ± 26 mL/min per 1.73m2) and chronic kidney disease-epidemiology collaboration (CKD-EPI) the lowest (76 ± 24 mL/min per 1.73m2). Consequently, the Mayo formula classified more patients (56%) as having normal renal function. There was a significant and strong correlation between the values obtained from all five formulas using Cockcroft-Gault as the reference formula: Mayo: r = 0.80, p < 0.001; CKD-EPI: r = 0.87, p < 0.001; modification of diet in renal disease (MDRD): r = 0.84, p < 0.001; inulin clearance-based: r = 0.99, p < 0.001). Multivariable analysis demonstrated that decreased renal function is an independent predictor of 3-year mortality in all five formulas, with risk increasing by 15–25% for each 10-unit decrease in eGFR. Despite the similarities between the formulas, the ability to predict mortality was highest in the Mayo formula and lowest in MDRD. Conclusions Our data suggest that while the Mayo formula is not currently recommended by any nephrology guidelines, it may be an alternative formula to predict mortality among patients with multivessel CAD, including to the widely used MDRD formula.